KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PIDANA DI BIDANG PERBANKAN - Sri Wulandari (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
Banking as one of the pillars of economic development in Indonesia,has the function of collecting and distributing public funds. Banking crimes are increasingly widespread, prohibited acts are regulated in Law no. 10 of 1998 concerning banking, prohibition is accompanied by threats (sanctions). The banking world has specific characteristics, so law enforcement is not merely enforcing positive laws, but it is necessary to involve the role of Bank Indonesia and the Directorate of Banking Compliance. The results show that banking crimes (TPP) are different from banking crimes (TPdBP), the scope of TPdBP is wider. Efforts to prevent and overcome TP in the banking sector are to use the chain of the criminal justice system, the legal process is intended to provide censure and deterrent effects for perpetrators and provide protection for the community